The Impact of Modern Retail on Traditional Retail Traders in The Mengwi, Badung District - Ni Ketut Seminari; Ni Made Rastini; Eka Sulistyawati (Udayana Journal of Social Sciences and Humanities, 2017)
Indomaret is a mini retail network that sells a variety of basic necessities as well as daily necessities. This retail uses overall system cost advantages or cost leadership. This cost advantage, making Indomaret ready to become a manufacturer with a low cost to the industry. Minimarket even this development is so rapid. This development was also accompanied public interest to shop at the minimarket is increased because of the opinion that the modern market (including minimarket) is neat, clean and practical than traditional retail. This thing become a big challenge for traditional retailers. This research is an observational research in a research objects within a certain period conducted in the traditional retail the title is Dampak Indomaret Terhadap Pedagang Ritel Tradisional di Desa Mengwi Kabupaten Badung. The purpose of this study was to determine their impact on traditional retail Indomaret including mini market in Mengwi. This study is a quantitative study using survey research methods. Survey research is a quantitative study using structured questions / systematic same to many people, then all the answers obtained by researchers recorded, processed, and analyzed. The results of research that Indomaret a significant impact on the existence of traditional retail merchants.